Family-based traditional market management in Yogyakarta Special Province Indonesia - Riyanti, Dwi; Yunianika, Ika Tri; Manik, Toba Sastrawan; Feriandi, Yoga Ardian; Suyatno (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
This research aims to examine the implementation of family-based principles in the traditional market management in Yogyakarta. This research is qualitative research employing a case study approach. Data collection methods were interviews and questionnaires. The research subjects consisted of Traditional Market Traders, Market Heads, and five Indonesian Association of Market Traders including Beringharjo, Sleman, Piyungan, Wates, and Wonosari Market.  The results of this research show that the family-based principles are applied in the management of these traditional markets. Based on the interview results and questionnaires, traditional market traders, market heads, and traders’ associations have a strong relationship both structurally and formally as well as culturally and informally. Communication between the three research subjects was established effectively by performing deliberations in policy making. Informal relationships include recitals, joint gymnastics, and cooperation. This study reveals that the value of deliberations is high which reaches 72%; a sense of family is 85.5%; Gotong-royong activity reaches 82%; family value reaches 83%; cultural value is 86%; and confidence level is 81%. This impacts the existence of Yogyakarta's traditional markets which still survive and even become tourist landmarks. This research has limitation on its depth and method usage, so future research needs to be deepened with other methods.